Bacaan Anak Tentang Indonesia Terbitan Amerika Serikat 1960-1980 - Sarumpaet, Riris K. Toha (UI Scholars Hub, 2002)
Children’s books about Indonesia published in the United States 1960-1980. The purpose of this study was to look at the image of Indonesia as presented in children’s literature published in the United States. The study focused upon the evaluative tone and the accuracy with which people in Indonesia are portrayed. Nineteen books (seven fi ctions, eight non-fi ctions, and four folktales) about Indonesia published between 1960 and 1980 constituted the sample of this study. In order to assess the quantitative portrayal of Indonesians in children’s books, the Evaluation Coeffi cient Analysis was used. A qualitative analysis was done using three evaluative criteria. The analysis of the data revealed that quantitatively, the books studied generally were positive in dealing with the image of Indonesians. Qualitatively, the fi ndings were interesting. Six books contained strong Western bias in measuring and depicting Indonesian people, and presenting the country in a negative tone as well. Stories and information about the picturesque and exotic predominated. Some otherwise fi ne books were spoiled by overgeneralization, stereotyping and inaccuracies in the text, illustration, and caption.